Contestations of Imperial Citizenship: Student Protest and Organizing in Qatar's Education City. (November 2020) - Al-Saleh, Danya; Vora, Neha
Abstract : Texas A&M, a public land grant university in College Station, Texas, has a long history of engagement with the Bush family. These ties highlight the university's entanglement with US imperial enterprises, which extend into the Persian Gulf. George H. W. Bush's own explanation of why he decided to place his presidential library at the campus despite not attending Texas A&M focused on these connections: "Over the years, Aggies have provided great service to the Armed Forces of our country. Patriotism abounds at A&M." Meanwhile, Qatar hosts the largest concentration of US troops abroad. The US military's Central Command is at Al Udeid Air Base, not far from the Education City complex that hosts TAMUQ and several branch campuses of American and other foreign universities. The students at these institutions are Qatari citizens, South Asian and Arab immigrants, and international students, primarily from Asia, Africa, and the Middle East.